Considerations on the Politico-Juridical Proceedings of Genesis 34 - Wagner, Angela B. (Journal for the study of the Old Testament, 2013)
In recent literature regarding the narrative of Genesis 34, much attention has been given to the nature of the force of the sexual encounter between the Hivite prince, Shechem, and the daughter of Jacob, Dinah. This article, however, argues that the concern with which this aspect of the narrative has been addressed is misplaced: that the violent response of Jacob and his sons has little to do with a distinction between consensual sex and violent rape and rather with political/ethnic concerns.